Sistem Pengisian Baterai VRLA 200Ah 24V Pada Pembangkit Listrik Tenaga Surya 6x100 Wp di PPYD Al-Ikhlas, Singosari, Kabupaten Malang - Gumilang, Binar Surya Gumilang; Djulihenanto, Saddani; Hermawan, Satria Luthfi; Andinia, Karenina Ledy; Wardania, Yasinta Ika (Politeknik Negeri Malang, 2024)
The electricity tariff is considered quite high in Indonesia for certain circles. One of them is PPYD Al-Ikhlas, Singosari, Malang Regency who experienced this. To overcome this, an electricity plant originating from solar energy was built at PPYD Al-Ikhlas that has maximum power of 600wp. Solar power plant that generates 24 hours / 7 days a week need battery system for storage the directly unused energy. The battery used is a Solana brand VRLA battery with a capacity of 100Ah/12V in a number of 4 pieces arranged in series-parallel, bringing the total capacity to 200 Ah/24V. Based on this thought, design and build a battery charging system with the aim of determining the components to be used and knowing the performance of the battery charging system. For charging the battery itself, it has become one with inverter hybrid with a capacity of 2400 Watts. From the testing after the installation of the components that have been carried out, the results show that this battery charging system uses a four-stage charging system method. From the data obtained, it can be seen average efficiency is 80,88%. So the efficiency of charging the battery in PLTS is considered good based on the data.